2013
DOI: 10.1021/jp311938u
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Desorption of Thiolates and Sulfur from Nanoparticle and Planar Platinum Surfaces

Abstract: Thiolate-protected platinum nanoparticles have become promising for applications in heterogeneous catalysis and the fabrication of new materials for hydrogen storage. Once nanoparticles have been synthesized and conveniently grafted onto a particular support, thiol removal might be required before its use. Here, thiolate and sulfur electrodesorption from nanoparticle and planar platinum surfaces are comparatively studied by combining ex-situ X-ray photoelectron spectroscopy (XPS) and electrochemical techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Thus, the analysis of the IR spectra of different alkanethiols on Pt shows a significant increase in the chain order as n increases, which is reflected in the shift of the dstretching vibration towards smaller frequencies (Figure 7 e-f). 150 Therefore, DT SAMs on Pt are well-ordered with a quality comparable to those found on Au. However, SAMs of shorter alkanethiols are more defective, less blocking, and have lower thiolate coverage than their Au counterparts.…”
Section: Surface Structures and Chemistrymentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the analysis of the IR spectra of different alkanethiols on Pt shows a significant increase in the chain order as n increases, which is reflected in the shift of the dstretching vibration towards smaller frequencies (Figure 7 e-f). 150 Therefore, DT SAMs on Pt are well-ordered with a quality comparable to those found on Au. However, SAMs of shorter alkanethiols are more defective, less blocking, and have lower thiolate coverage than their Au counterparts.…”
Section: Surface Structures and Chemistrymentioning
confidence: 84%
“…This shift was also observed for DT-protected PtNPs and disappeared after electrochemical cleaning (Figure 7h). 150 On the other hand, it was reported that PtNPs protected by TMA and prepared by the Kimura synthesis exhibit significant amounts of Pt(I), suggesting the presence of a Pt(0) core surrounded by Pt(I)thiolates on the surface. 164 Table 5 Geometric and energetic parameters for the different Pt surface structure models discussed in the text and figures In conclusion, there is no experimental evidence of Pt surface reconstruction upon thiol adsorption, and thus simple adsorbate models could be valid to describe this system.…”
Section: Surface Structures and Chemistrymentioning
confidence: 99%
“…It was previously reported that atomic hydrogen is produced in situ on clean platinum electrodes with potentials V e < À0.6 Vb yt he Volmer reaction:H 2 O + e À = H ad + OH À .T his reaction provides the atomic hydrogen required to break the thiolate-platinum bond according to the reaction:R S-Pt + H = RSH + Pt. [17] We found that an applied potential of V e = À1V(vs. Ag/AgCl) provides effective thiolate removal, while not producing excessively large bubbles due to hydrolysis of water,a nd was used for all experiments unless otherwise noted.…”
Section: Methodsmentioning
confidence: 88%
“… 22 These advantages have been also confirmed by a study of alkane thiolate-protected Pt nanoparticles (NPs), showing that adsorbed sulphur species on Pt surfaces are indeed very stable against desorption even at high reduction potentials. 23 Ligand coated surfaces are usually undesirable in electrocatalysis because the charge transfer between catalyst and reactant can be significantly slower, or completely shut down depending on the length of the ligand. 21 b In our case, we want to inhibit as much as possible the electron transfer at the monolayer modified sections of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Floridia et al found out that medium (hexanethiol, C 6 -SH) and long (dodecanethiol, C 12 -SH) chain thiols adsorbed on Pt NPs exhibit similar stability against desorption at high reduction potentials (up to À1.8 V vs. SCE), but the quality of the self-assembled monolayers (SAMs) strongly depends on the chain length, with longer chains leading to higher coverage. 23,24 Taking into account also solubility problems, encountered for long-chain thiols, one can conclude that, as a compromise, an intermediate chain length might be optimal to modify the mesoporous Pt surfaces. Accordingly, heptanethiol (C 7 -SH) was selected for functionalizing the external surfaces of chiral-imprinted mesoporous Pt electrodes.…”
Section: Surface Functionalization With Thiol Moleculesmentioning
confidence: 99%